The “Body” of Dionysos and Its Preannouncements: Theatre as an Ecumenical Diasporic Phenomenon - Moudatsakis, Tilemachos (Études helléniques / Hellenic Studies, 2008)
The ecumenical character of the theatre seems to be preannounced in the bloody adventures of Dionysus, the god of the main performance space, who moves continuously throughout the “global expanse” (χώρος οικουμένης) creating miracles (exploits), sometimes becoming an aggressor, sometimes an extraordinary fabulous victim. The crowning moment of his career during his undeterred wanderings – occurred at Icaria, the island where he had been captured by the Tyrrhenians – the famous pirates who, ignoring the divine nature of their victim, sold him as a slave in Asia. Dionysus then established the first scenography in theatre mythology. A magical vine grew on the deck while the oars of the pirates’ ship were transformed into snakes. The ecumenical and diasporic character of the theatre is also heralded by Aeschylus’ journeys in 470 BC to Sicily where he performed The Persians and wrote a new tragedy inspired by the area, The Women of Aitna.